The art of voice-acting : the craft and business of performing for voice-over - Alburger, James R., 1950- 4 0 16; 5 (Boston : Focal Press, 1999)
Describes the steps involved in learning the performing skills needed to be successful in the voice-over business, and provides information on how to get a demo tape produced and into the right hands.
Includes bibliographical references (p. 228-230).
Adult;Adult
Keywords: 2 -- 0; 6; Vocational guidance.;Vocational guidance.;Vocational guidance.;Vocational guidance.;Vocational guidance.;Vocational guidance.;Vocational guidance.;Vocational guidance. -- Television announcing;Radio announcing;Voice-overs.;Television advertising;Radio advertising;Television announcing;Radio announcing;Television advertising;Radio advertising;Vocational guidance; 20; 2